Kualitas Pelayanan dan Harga Terhadap Keputusan Pembelian Produk Mcdonald’s Pondok Cabe - Satria Sultan Ikbari; Alda Arsikoh; Yusril Mardani (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
In South Tangerang there are several fast food restaurants, one of which is McDonald's. The most important thing in a business is to get a buying decision. The researcher formulates the research problems as follows: 1.) Does service quality affect purchasing decisions? 2.) Does the price affect the purchase decision?. This study aims to determine the level of purchasing decisions on service quality and prices at McDonald's Pondok Cabe Restaurant. This research was conducted from October to November 2022. The population in this study were people who had bought and eaten directly at a McDonald's Restaurant. samples taken as many as 105 respondents using systematic random sampling method. The research approach used in this research is descriptive analysis using questionnaire data with a sample of 105 respondents. The analysis technique used is multiple linear regression. The results of this study state that: The results of the partial test (t test) show that (1) service quality has no effect on purchasing decisions, (2) Price has a significant effect on purchasing decisions, (3) that service quality and price simultaneously (f test) significantly influence the decision to purchase McDonald's Pondok Cabe products.